2016
DOI: 10.5433/1679-0359.2016v37n1p131
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da temperatura e umidade durante o armazenamento semi-hermético sobre parâmetros de avaliação da qualidade dos grãos e do óleo de soja

Abstract: The soybean (Glycine max (L.) Merrill) is the most cultivated oilseed in the world, being of major importance in food, feed and biodiesel production. The quality of the product being marketed is directly influenced by storage techniques, and the grain moisture, temperature and storage time are primarily responsible for most of the amendments. The aim of this study was to evaluate the effects of temperature and humidity during the semi-hermetic storage on chemical and technological parameters for assessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…It is found that the parameter a* was not influenced by the storage period (p> 0.05), so that the mean values were positive, indicating that the grains presented a greater presence of green color (Figure 6), which was demonstrated in the 3, since parameter a* varies from red to green on a scale from (+60) to (-60). These effects that Ziegler (2014) observed in his experiment, stating that the relative humidity influences more than the temperature for maintaining the color in storage.…”
Section: Resultsmentioning
confidence: 70%
“…It is found that the parameter a* was not influenced by the storage period (p> 0.05), so that the mean values were positive, indicating that the grains presented a greater presence of green color (Figure 6), which was demonstrated in the 3, since parameter a* varies from red to green on a scale from (+60) to (-60). These effects that Ziegler (2014) observed in his experiment, stating that the relative humidity influences more than the temperature for maintaining the color in storage.…”
Section: Resultsmentioning
confidence: 70%
“…Essentially, the ideal grain moisture content for the commercialization and storage is between 13% and 15.5%, varying according to the agricultural product type and the storage conditions and time (Coradi et al, 2016; Martinez‐Feria et al, 2019). High moisture levels drastically affect the grain physicochemical and morphological properties, such as the acidity content and the extracted oil quality (Ziegler, Marini, et al, 2016). The soybean grain drying at high temperatures causes rupture in the grain structure, favoring fungi infection and increasing the conversion of important chemical elements into undesirable products (Ferreira et al, 2019; Ziegler, Vanier, et al, 2016).…”
Section: Drying Technologymentioning
confidence: 99%
“…Nos grãos armazenados com teor de água de 12 e 14%, aos 180 dias não houve diferença significativa entre as três temperaturas estudadas. Os resultados estão de acordo com Ziegler (2014), que armazenou soja durante doze meses e verificou que altas umidades de grãos e altas temperaturas intensificam a redução do pH. Rehman et al (2002) armazenando grãos de milho em três condições de temperatura verificaram redução do pH dos grãos ao final dos seis meses de armazenamento nas temperaturas de 25 e 35ºC.…”
Section: Figura 1 -Efeitos Do Tempo De Armazenamento No Teor De áGua unclassified